Intensive Prayers: Prayer as a Weapon and Relationship Among the Emerging Generations of African Diaspora Churches in the UK - Caleb Nyanni; Oliver Andoh-Kesson (Religions)
The proliferation of African diaspora churches, especially over the last four decades in Europe and the West, has not gone unnoticed. Over this period, there has been a planting and transporting of independent churches as well as branches of Pentecostal and charismatic churches from sub-Saharan Africa to the West. First-generation members of these churches have often been the pioneers, leaders, and custodians of the church culture and practices from their motherland. These first-generation members continue to hold on to liturgy and practices from ‘home’ (Africa) and seek to replicate them as authentic spirituality and spiritual formation practices. A significant part of the rise of these churches are the second-generation members who have a fluid identity and are finding newer ways to assimilate their parents’ socio-cultural and religious practices with that of their present ‘home’ European/Western nations. For these emerging-generation members, their parents’ culture, which is largely based on an African worldview, continues to shape church liturgy and practices. An integral component of the church’s liturgy and practical ministry is prayer. Prayer in its various forms plays a significant part in both personal and collective worship. This paper examines the impact of emerging generations on the dynamics and praxis of prayer in the Church of Pentecost UK. Prayer holds a significant place in the lives of these emerging generation members and forms part of their socio-religious identity. Against this backdrop of prayer from a generational and liturgical viewpoint, we explore the nature, dynamics, and context of the prayers of the emerging generation members of the Church of Pentecost, UK. We examine areas of continuity and discontinuity and explore how Western influences and modernisation have influenced the prayer language and style of the younger generation. Through participant observations and lived experiences, we argue that though prayer is central to the worship of the younger generation, there are significant variations between the generations within the broader framework of style, language, and content.